Andrographolide inhibits osteopontin expression and breast tumor growth through down regulation of PI3 Kinase/Akt signaling pathway - Kumar, S.; Patil, H. S.; Sharma, P.; Kumar, D.; Dasari, Sreekanth; Puranik, Vedavati G.; Thulasiram, H. V.; Kundu, G. C. (Current Molecular Medicine, 2012)
Breast cancer is one of the most common cancers among women in India and around the world. Despite recent advancement in the treatment of breast cancer, the results of chemotherapy to date remain unsatisfactory, prompting a need to identify natural agents that could target cancer efficiently with least side effects. Andrographolide (Andro) is one such molecule which has been shown to possess inhibitory effect on cancer cell growth. In this study, Andro, a natural diterpenoid lactone isolated from Andrographis paniculata has been shown to inhibit breast cancer cell proliferation, migration and arrest cell cycle at G2/M phase and induces apoptosis through caspase independent pathway. Our experimental evidences suggest that Andro attenuates endothelial cell motility and tumor-endothelial cell interaction. Moreover, Andro suppresses breast tumor growth in orthotopic NOD/SCID mice model. The anti-tumor activity of Andro in both in vitro and in vivo model was correlated with down regulation of PI3 kinase/Akt activation and inhibition of pro-angiogenic molecules such as OPN and VEGF expressions. Collectively, these results demonstrate that Andro may act as an effective anti-tumor and anti-angiogenic agent for the treatment of breast cancer.
Keywords: Andrographolide; angiogenesis and breast tumor; migration; osteopontin; PI 3 kinase